Molecular Epidemiology and Antimicrobial Resistance Gene Distribution in Neisseria gonorrhoeae Isolates from Cervicitis Cases (Bangladesh Journal of Infectious Diseases, 2025)
Background: Cervicitis is frequently caused by sexually transmitted infections (STIs), including Neisseria gonorrhoeae, Chlamydia trachomatis and Trichomonas vaginalis. The emergence of antimicrobial resistance (AMR) in N. gonorrhoeae presents significant treatment challenges, making it essential to monitor the molecular epidemiology and resistance profiles of this pathogen.Objective: This study was aimed to investigate the molecular epidemiology, antimicrobial resistance patterns, and the prevalence of Neisseria gonorrhoeae in cervicitis cases, with a focus on detecting resistance-associated genes and the co-occurrence of other STIs, including HPV.Methodology: This cross-sectional study was conducted in the Department of Microbiology, Dhaka Medical College, Bangladesh, with sample collection from the gynaecology outpatient department between January and December 2017, and included female patients with clinically suspected cervicitis. A total of 248 cervical swab samples were collected from women with cervicitis. The samples were analyzed using Gram staining, bacterial culture, PCR, and antimicrobial susceptibility testing. PCR was also employed to detect resistance-related genes and HPV strains in cervical biopsy specimens.Results: Of the 248 cervical swab samples, Neisseria gonorrhoeae was detected in 10.48% of cases. Antimicrobial resistance testing revealed high levels of resistance to Ciprofloxacin (92.86%) and Tetracycline (85.71%) among the N. gonorrhoeae isolates, with 57.14% also resistant to Doxycycline. Notably, all isolates remained susceptible to Ceftriaxone and Cefixime, which continue to be highly effective for treatment. Penicillinase-producing N. gonorrhoeae strains were identified in 71.42% of cases, indicating ongoing selective pressure for resistance. PCR analysis also revealed the presence of resistance-associated genes, including penA, mtrR, and porB. In addition, HPV DNA was detected in 16.66% of cervical biopsy samples, with HPV-16 identified in 13.33% and HPV-18 in 3.33%. Co-infection with other STIs was observed in 25.40% of the N. gonorrhoeae-positive cases.Conclusion: Neisseria gonorrhoeae remains a significant cause of cervicitis with high resistance to common antibiotics. Regular surveillance of antimicrobial resistance is crucial for treatment management. The study also emphasizes the importance of HPV vaccination to reduce cervical cancer risk, particularly for HPV-16 and HPV-18.Bangladesh Journal of Infectious Diseases, June 2025;12(1):42-51